Biology and habits of Mahanarva andigena (Hemiptera: Cercopidae) under screenhouse conditions - RODRÍGUEZ-CH., JAIRO; PECK, DANIEL C. (Revista Colombiana de Entomología, 2007)
Mahanarva andigena was detected in Colombia for the first time in 1999, in the municipality of Tumaco (Nariño), on the south Pacific coast, associated with the hosts Sorghum halepense and Saccharum officinarum. In order to complement studies aimed at an understanding of the biology of other species of spittlebugs associated with cultivated grasses in Colombia, this research was designed to establish an initial base on the morphological differentiation, duration of the developmental stages, and certain aspects of the reproductive biology. The morphological studies permitted the differentiation and characterization of the egg, nymph and adult, at the same time determining the duration of the life cycle under semi-controlled conditions. For the eggs (27°C, 100% R. H.), the mean time to eclosion was 16.4 days. For the nymphs (mean temperature min/max 19.5/29.9°C, 95% R. H.) the mean development time was 48.4 days, divided in 6.4, 8.6, 8.2, 10.1 and 15.1 days for the five instars, respectively. For the adults (mean temperature min/max 19.5/29.9°C, 95% R. H.), the mean longevity was 21.4 days, 25.6 days for the females and 18.3 days for the males. Under the conditions of the study, the total duration of the life cycle of M. andigena was 75.5 days. M. andigena exhibited a flexibility for oviposition substrate, with a preference for uncovered soil with 51.2% of the recovered eggs; 16.4, 32.4 and 0% were recovered from soil under litter, surface of the stem, and the litter, respectively. The information provided strengthens certain patterns established for the spittlebug complex in grasses and broadens our understanding of the biological variation. As the first study on a spittlebug species associated with sugar cane in Colombia, a base line is established for biological studies of spittlebugs as emerging pests of the sugar cane industry.